STRATEGI PERENCANAAN DAN PENGEMBANGAN INDUSTRI PARIWISATA DENGAN MENGGUNAKAN ANALISIS SWOT - Rikah Rikah; Muhammad Tahwin; Hetty Muniroh (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2017)
The development of tourism in an area brings the impact of benefits to society economically and socially and culturally. Rembang Regency has many attractions including attractions Dampo Awang Beach. It takes a proper strategy in influencing tourists interest to the attractions of Dampo Awang Beach. This research is a qualitative descriptive study that conducts assessment on alternative strategy of planning and development of Dampo Awang Beach attraction based on internal and external factor analysis. Population in this research is visitor of Dampo Awang Beach tourism object with research method with SWOT analysis approach. The results of this study are internal and external factors affect the level of visits on the attraction of Dampo Awang Beach is very large. SWOT analysis is a planning and development strategy that can be applied to the attractions of Dampo Awang Beach